SEGMENTASI PENGUNJUNG KAWASAN ISTANA SIAK DI KABUPATEN SIAK SRI INDRAPURA - Ana Sulfiana; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Siak Regency has tourism potential such as natural tourism, cultural tourism, religious tourism and historical tourism. One of the most visited enthusiasts every year is the Historical Tourism Object, the Siak Palace. Therefore, this study was conducted to find out Visitor Segmentation in the Siak Palace area so that tourist attractions can increase tourist visits each year. This study aims to determine how the Visitor Segmentation of Siak Palace Area in Siak Sri Indrapura Regency. This research uses descriptive qualitative method by collecting data in the form of words, pictures, and describing or describing phenomena that exist, both scientific phenomena and human engineering, this method is able to explain phenomena through collecting data obtained through interviews, any data that can be processed and published clearly using language that is easily understood. Data collection techniques in this study used observation, interviews, documentation and questionnaires. The sample in this study was 100 samples using the Slovin formula. Measurement data using a Likert scale to determine the length of the short interval. Based on the results of this study, Visitor Segmentation of the Siak Palace Area in Siak Regency with sub-variables Geographic Segmentation, Demographic Segmentation, Psychographic Segmentation, and Consumer Behavior Segmentation.                                                                                   Keywords: Visitor Segmentation, Siak Palace